Financial Stability Reports : What Are they Good for? - Munoz, Sonia (IMF Working Papers; Working Paper, 2012)
The global financial crisis has renewed policymakers' interest in improving the policy framework for financial stability, and an open question is to what extent and in what form should financial stability reports be part of it. We examine the recent experience with central banks' financial stability reports, and find?despite some progress in recent years?that forward-looking perspective and analysis of financial interconnectedness are often lacking. We also find that higher-quality reports tend to be associated with more stable financial environments. However, there is only a weak empirical link between financial stability report publication per se and financial stability. This suggests room for improvement in terms of the quality of financial stability reports.